Understanding Food Hygiene Practices and Food Safety among Manufacturers towards Aflatoxins Contamination in Peanut-based Products - Nur Nazurah Mohd Azaman; Nitty Hirawaty Kamarulzaman; Mad Nasir Shamsudin; Jinap Selamat (International Journal of Supply Chain Management, 2015)
Aflatoxins are naturally mycotoxins occurring found in human foods and animal feeds and are highly carcinogenic in many experimental studies. Agricultural produce like peanuts is prone to aflatoxins contamination, particularly during crop growth periods, harvesting, and drying. Aflatoxins contamination can cause by improper storage condition or pest infestation that favorable to growth of Aspergillus fungi. With certain preventive practices along the length of groundnut or peanut-based products chain can help to reduce the risks of aflatoxins contamination. The purpose of this study was to determine the attitude of the food hygiene practices and food safety of aflatoxins contamination among peanut-based products manufacturers. Face-to-face interviews were carried out using a semi-structured questionnaire with 44 manufacturers. Data was analyzed using mean score analysis and logistic regression. The total mean score analysis revealed that most of the manufacturers had general knowledge about aflatoxins contamination and food safety (2.695). Meanwhile, the total mean score for attitude showed a favorable attitude towards aflatoxins contamination and food safety (4.254) among the manufacturers. Most of the manufacturers follow food safety and hygiene practices towards aflatoxins contamination in producing peanut-based products (2.744). Results from logistic regression analysis indicated that knowledge (p=0.081), attitude (p=0.055), and employee training (p=0.099) have a significantly positive relationship towards hygiene practices and food safety among the manufacturers. There is a need for the manufactures to have proper and continuous training for their workers in ensuring basic principles of food safety and important rules of food handling in personal hygiene and sanitation are followed and be as part of their social responsibilities for serving the safe and quality of food products to consumers.